THE SUPPLY OF FISH SEED FOR FLOATING NET CAGES IN THE TANJUNG SANI VILLAGE TANJUNG RAYA SUB-REGENCY AGAM REGENCY WEST SUMATRA PROVINCE - Tisno '; Hendrik '; Kusai ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Research on the supply of fish seed for this Floating Net Cage was held in March 2015 in Tanjung Sani Village. The purpose of this study was to determine the origin of seeds is also the number of seeds for one year and to know how the seed marketing chain, and this study also aims to determine the price of the seed at the level of producers and consumers.The results showed that the seeds supplied from Koto Malintang, Bayur, Lubuk Basung, and from Tanjung Sani it self. Within one year of Tilapia fish seed is supplied 70.956 million, and 22.518 million fish Mas seed . Marketing seed from outside through an intermediary supplier and the seed of the Tanjung Sani directly to consumers. The price of Tilapia fish seed from suppliers is Rp 110 / seed, while from fish farmer is Rp 100 / fry, the price of fish Mas seed of supplies is Rp 115 / seed, while from seeding is Rp 105 /seed.Keywords: Seed Supply,Floating Net Cage, Pricing, Marketing Chain